Crisis decade : looking into the eighties : a pamphlet - Laidlaw, Ken; Laishley, Roy (London: ICDA, 1980)
"By the International Coalition for Development Action ; in collaboration with the United Nations non-Governmental Liaison Service ; with the support of UNDP and UNESCO ; text by : Ken Laidlaw, Roy Laishley"